الشيخ محمد نووي البنتني الجاوي المكي وجهوده الدعوية في القرن التاسع عشر الميلادي - Imawan, Dzulkifli Hadi (The International Journal of Pegon : Islam Nusantara civilization, 2018)
This paper is about to discuss a scholar of Nusantara in Haramain who has a major role in the development of da’wah and intellectuals in the Islamic world in the 19th century ADthe 19th-20th century AD was the golden age of the scholar of Nusantara in Haramain because of the quantity and quality of those who did not exist before or since. But the traces of their da’wah are not widely known by the present generation like Shaykh Muhammad Nawawi al-Bantani. Therefore, thisstudy will discuss the history of one of Nusantara scholar in Haramain, Shaykh Muhammad Nawawi al-Bantani by taking the focus of his study of dakwah and his intellectual contribution in the Islamic world.The study used is a study of literature on the biography of Haramain scholars, especially the literary sources that discussed Shaykh Nawawi al-Bantani. the results of this study suggest that Shaikh Muhammad Nawawi al-Bantani was a great Haramain scholar who came from the archipelago, and he was well known by the Haramain scholars of his time. he has spent his life to preach both verbally (ta’lim), writings (kitabah), and examples (qudwah) by clinging to al-sunnah waal-jamaah’s manhaj in aqidah, Shafi’s school in Sharia and Sunni tasawuf. From the influence of his da’wah, he has given birth to many great scholars and many helpful Islamic repertoire both materially and intellectually.